Kualitas Air dan Karakteristik Tanah Penduga Erodibilitas pada Sub-Sub DAS Amandit Kabupaten Hulu Sungai Selatan - Muhammad Rizal; Zuraida Titin Mariana; Bambang Joko Priatmadi (Acta Solum, 2024)
Land management in, Amandit sub-sub watershed must comply with the principles of soil and water conservation to avoid erosion and sedimentation. The aim of this research was to assess water quality and soil characteristics that predict erosion in the upstream, middle and downstream areas. The purposive sampling method was used by taking soil and water samples in the upstream, middle and downstream parts. In the upstream section soil samples were taken with a slope of 15-25%, in the middle section with a slope of 8-15% and in the downstream section with a slope of 0-8%. Soil samples were taken at each of six points representing the upstream, middle, and downstream parts of the area. Water sampling was carried out in the soil sampling area by paying attention to the slope of the land. The results showed that the water quality (pH, DHL, SAR, and TSS) in the area was in accordance with the quality of water for irrigation. Soil erodibility values in the upper and middle areas did not show significant differences. In the upstream part, soil erodibility had very low criteria and the middle part had low criteria but were different from the downstream area (medium criteria).